Water circulation pattern from sea surface current and chlorophyll-a derived using satellite data in the South China Sea - Seeni Mohd., Mohd. Ibrahim; Ahmad, Samsudin; Fung, Fook Wah; Kueh, Hsiao Chin (2005)
Remote sensing satellite data is useful in chlorophyll-a concentration and sea surface current mapping applications. This paper reports on a study carried out to analyze the water circulation pattern from the generated sea surface current velocity and chlorophyll-a concentration during the monsoon seasons from remote sensing data. Merged Sea Level Anomaly (MSLA) with Orbit Error Reduction merged satellite altimetry data set used to generate the velocity vector map by using the geostrophic velocities method over the South China Sea (SCS). The frequent MSLA data which is provided by the AVISO server twice per-week is useful for sea surface current studies. The sea surface current velocity vectors are mapped in 1/3o Mercator projection. Multitemporal Moderate Resolution Imaging Spectriradiometer (MODIS) daily data were used in the chlorophyll-a concentration mapping. The correlation between sea surface current and chlorophyll-a during the monsoon seasons is approximately 0.7-0.8 in the South China Sea. The sea surface current circulation during the north-east monsoon is anti-clockwise at the middle of SCS, however it is clockwise off the coast of Terengganu and Gulf of Thailand. For the inter-monsoon, the circulation pattern of the middle of SCS is clockwise and it is ati-clockwise off the coast of Terengganu and Gulf of Thailand.for the south-west monsoon, the circulation pattern is clockwise off the coast of Terengganu and Gulf of Thailand. However, it is approximately in a upward direction from south to north with clockwise water circulation pattern in the middle of SCS. The knowledge on sea surface current and chlorophyll-a concentration is important in fisheries and ocean science studies.